Gambaran Pengolahan Air Limbah Rumah Sakit Jiwa Daerah Provinsi Lampung Tahun 2020 - Tri Fitria Ulfa; Imam Santosa; Haris Kadarusman; Ferizal Masra (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2020)
The hospital is one of the efforts to improve health consisting of medical centers and doctors' offices which are also supported by other units, such as operating rooms, laboratories, pharmacy, administration, kitchen, laundry, waste and waste treatment, as well as organizing education and training . The purpose of this study was to determine the description of wastewater treatment in Lampung Province Mental Hospital in 2020. The type of this research was a descriptive study using qualitative methods, with the object of research being the entire wastewater treatment system of Lampung Province Mental Hospital in 2020. Data collection obtained through observations and observations of the condition of the drainage of wastewater treatment, and interviews with related sections, namely the sanitation department and WWTP officers of Lampung Province Mental Hospital about the wastewater treatment process. From the results of the research that has been done, it can be seen in the treatment of wastewater in the Lampung Provincial Mental Hospital that has not gone well. In the treatment of wastewater treatment plants WWTP off, the wastewater from laundry is not flowed to WWTP, the inspection of wastewater quality is not in accordance with established regulations.